Indonesia and the Philippines : political dynasties in democratic states - Yoes, C. Kenawas (2013)
The growth of political dynasties poses a serious challenge to the democratic consolidation in the Philippines and Indonesia. However, the needed reforms to prevent political dynasties from monopolising electoral politics in both democracies remain elusive.